2017
DOI: 10.1038/s41467-017-01669-z
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus-reactive CD8+ T cells mediate cross-protection against subsequent Zika virus challenge

Abstract: Zika virus (ZIKV) and dengue virus (DENV) are antigenically related flaviviruses that share cross-reactivity in antibody and T cell responses, and co-circulate in increasing numbers of countries. Whether pre-existing DENV immunity can cross-protect or enhance ZIKV infection during sequential infection of the same host is unknown. Here, we show that DENV-immune Ifnar1 −/− or wild-type C57BL/6 mice infected with ZIKV have cross-reactive immunity to subsequent ZIKV infection and pathogenesis. Adoptive transfer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
138
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 73 publications
(99 reference statements)
6
138
1
2
Order By: Relevance
“…However, recent results from our group and others have shown that previous flavivirus exposure-including DENV-may have no detrimental impact on ZIKV infection in vivo in non-human primates (NHP) 17,18 and humans 19 . Moreover, these studies and others suggest that previous DENV immunity may play a protective role during ZIKV infection involving humoral and cellular responses [20][21][22][23][24] . On the other hand, little is known about the opposite scenario, the role of a previous ZIKV exposure on a subsequent DENV infection, which is relevant to anticipate the dynamics of forthcoming DENV epidemics.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, recent results from our group and others have shown that previous flavivirus exposure-including DENV-may have no detrimental impact on ZIKV infection in vivo in non-human primates (NHP) 17,18 and humans 19 . Moreover, these studies and others suggest that previous DENV immunity may play a protective role during ZIKV infection involving humoral and cellular responses [20][21][22][23][24] . On the other hand, little is known about the opposite scenario, the role of a previous ZIKV exposure on a subsequent DENV infection, which is relevant to anticipate the dynamics of forthcoming DENV epidemics.…”
Section: Introductionmentioning
confidence: 70%
“…Early studies of T cells associate their contribution towards immunopathogenesis in DENV secondary infections explained by the original antigenic sin 59 , but increasing evidence suggest their protective role during primary and secondary DENV infections 60 . Recently, with the introduction of ZIKV into The Americas, T cells from DENV immunity are being implicated in mediating cross-protection against ZIKV [22][23][24] . However, the role and kinetics of T cells from ZIKV immunity in a subsequent DENV infection remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of the cellular immune response controlling the viral burden of ZIKV in mice has been reported (76, 77). More recently mouse models have shown that prior DENV immunity can protect against ZIKV infection during pregnancy, and CD8+ T cells are sufficient for this cross-protection (78).…”
Section: Discussionmentioning
confidence: 99%
“…However, our study demonstrated that the highest average force of infection values are found in provinces with mean temperatures between 20 and 26°C (Table 1), and laboratory studies confirm that Zika virus can be detected in the salivary glands of Aedes aegypti and transmitted at 25°C [63]. There are several possible hypotheses that could explain this discrepancy, including that: 1) provinces with mean temperatures around 29°C already implement vector control; 2) people may have acquired cross-immunity from exposure to other arboviruses [25,64,65]; and/or 3) given suitable temperature for transmission, other factors that can covary with temperature such as land use, urbanization, and socioeconomics may be more important drivers of large epidemics [20]. These hypotheses raise important questions about how to reconcile and ground truth theoretical and empirical studies with field data.…”
Section: Discussionmentioning
confidence: 99%